1997
DOI: 10.1074/jbc.272.14.9517
|View full text |Cite
|
Sign up to set email alerts
|

DNA Secondary Structures and the Evolution of Hypervariable Tandem Arrays

Abstract: Tandem repeats are ubiquitous in nature and constitute a major source of genetic variability in populations. This variability is associated with a number of genetic disorders in humans including triplet expansion diseases such as Fragile X syndrome and Huntington's disease. The mechanism responsible for the variability/instability of these tandem arrays remains contentious. We show here that formation of secondary structures, in particular intrastrand tetraplexes, is an intrinsic property of some of the more u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
38
0

Year Published

1998
1998
2009
2009

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(40 citation statements)
references
References 72 publications
(70 reference statements)
2
38
0
Order By: Relevance
“…It was shown recently that the progression in vitro of AMV reverse transcriptase along insulin-like growth factor II mRNA is blocked at a guanine-rich region that forms a quadruplex domain and two stable hairpins (Christiansen et al, 1994). Similarly, the progression in vitro of a variety of DNA polymerases along a guanine-rich region in the ␤ globin promoter DNA is arrested at an intrastrand tetraplex-forming sequence (Woodford et al, 1994). Last, expansion of the trinucleotide (CGG) repeat stalls the progression of the 40 S ribosomal subunit during the translation of FMR1 mRNA (Feng et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was shown recently that the progression in vitro of AMV reverse transcriptase along insulin-like growth factor II mRNA is blocked at a guanine-rich region that forms a quadruplex domain and two stable hairpins (Christiansen et al, 1994). Similarly, the progression in vitro of a variety of DNA polymerases along a guanine-rich region in the ␤ globin promoter DNA is arrested at an intrastrand tetraplex-forming sequence (Woodford et al, 1994). Last, expansion of the trinucleotide (CGG) repeat stalls the progression of the 40 S ribosomal subunit during the translation of FMR1 mRNA (Feng et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, guanine-rich tracts of RNA or DNA that fold back to generate a hairpin (Christiansen et al, 1994) or tetraplex structure (Christiansen et al, 1994;Woodford et al, 1994) were shown to arrest DNA synthesis in vitro. If formed in vivo along single strand stretches, back-folded d(CGG) n structures may also obstruct DNA transcription and replication.…”
Section: Expansion Of a D(cgg)mentioning
confidence: 99%
“…These oligodeoxyribonucleotides were then used together with a primer that contained an EcoRI site and 15 bases complementary to the 3Ј-end of the supF gene to generate a PCR fragment as described previously (9,14). For PCR fragments containing inosine or 7-deazaadenine, dITP or 7-deaza-dATP was substituted for the appropriate dNTP in the PCR.…”
Section: Template Preparation-oligodeoxyribonucleotides Containing Anmentioning
confidence: 99%
“…For PCR fragments containing inosine or 7-deazaadenine, dITP or 7-deaza-dATP was substituted for the appropriate dNTP in the PCR. For the construction of plasmid templates, the PCR product was digested with EcoRI, purified by gel electrophoresis, and then cloned into the plasmid pMS189⌬ as described previously (9,14). Plasmids were propagated in E. coli MBM7070, isolated by alkaline lysis, and purified by CsCl * The costs of publication of this article were defrayed in part by the payment of page charges.…”
Section: Template Preparation-oligodeoxyribonucleotides Containing Anmentioning
confidence: 99%
“…We have recently described the presence of a strong K ϩ -dependent DNA synthesis arrest site in a G-rich region of the chicken ␤-globin gene promoter (18). The sequence of the arrest site is shown in boldface type in Fig.…”
mentioning
confidence: 99%